Phenobarbital pharmacokinetics in neonates and infants during extracorporeal membrane oxygenation - Pokorná, Pavla; Šíma, Martin; Vobruba, Václav; Tibboel, Dick; Slanař, Ondřej (Perfusion, 2018)
INTRODUCTION: The disposition of drugs is potentially changed due to extracorporeal membrane oxygenation (ECMO) in neonates and infants. METHODS: The aim of the study was to evaluate the individual pharmacokinetics (PK) of phenobarbital and the effect of PK covariates in neonates and infants undergoing ECMO. Sixteen patients (7 neonates, 9 infants) treated with phenobarbital during ECMO (centrifugal-flow pump circuits) were enrolled in the PK study. Phenobarbital serum concentrations were measured using a fluorescence polarization immunoassay. Individual PK parameters - volume of distribution (Vd) and clearance (CL) were calculated in a one-compartmental pharmacokinetic model. RESULTS: The mean (SD) Vd and CL values in neonates were 0.46 (0.24) L/kg and 8.0 (4.5) mL/h/kg, respectively. Respective values in infants were 0.56 (0.23) L/kg and 8.5 (3.1) mL/h/kg. PK parameters in neonates and infants were not significantly different. We observed high inter-individual variability in PK parameters (coefficients of variation [CV] were 52% and 53% for CL and Vd, respectively). Doses were adjusted based on therapeutic drug monitoring (TDM) in 87.5% patients. Only 50% of the first measured phenobarbital serum concentrations in each patient were within the therapeutic range of 10-40 mg/L, in comparison with 88.6% concentration measured after TDM implementation. Linear regression models showed that both Vd and CL are significantly related with body weight (BW) and length. Median optimal phenobarbital loading dose (LD) and maintenance dose (MD), calculated from pharmacokinetic data, were 15 mg/kg and 4 mg/kg/day, respectively. CONCLUSIONS: Body weight was shown to be the main PK covariate of phenobarbital disposition. Subsequent dosing nomograms are provided for phenobarbital dosing during ECMO.
Keywords: Male; fenobarbital; Infant; phenobarbital; mužské pohlaví; pharmacotherapy; infants; novorozenec; mimotělní membránová oxygenace; Phenobarbital; lidé; ženské pohlaví; pharmacokinetics; Humans; Extracorporeal Membrane Oxygenation; Infant, Newborn; kojenec; ECMO; Female